A priori estimates of the electrohydrodynamic waves with vorticity: horizontal electric field. Issue 3 (11th February 2023) - Yang, Jiaqi
ABSTRACT: In this paper, we are concerned with an incompressible and inviscid conducting fluid in the presence of surface tension and horizontal electric field. It is obtained the local-in-time estimates on the interface in H ( 3 / 2 ) k + 1 and the velocity fields in H ( 3 / 2 ) k by using the method introduced by Shatah and Zeng [A priori estimates for fluid interface problems. Commun Pure Appl Math. 2008;61(6):848–876]. The estimates of a horizontal electric field can be obtained from the estimates of the interface and elliptic estimates.